An Investigation on principle biochemical components, photosynthetic pigments, nucleic acid and enzymatic activities of axenic culture of Scytonema sp. treated with two PAHs: Acenapthene and Fluoranthene - Patel, Miral; J.I, Nirmal Kumar; Tiwari, K. K. (International Journal of Applied Sciences and Biotechnology, 2014)
The fresh water cyanobacteria Scytonema sp. was cultivated in a laboratory scale in the presence of various concentrations (2.5, 5, 10, 20 ppm) of two polycyclic hydrocarbons in order to assess the influence of the pollutant on the growth and certain physiological responses of the cyanobacteria. The algal cells were analyzed for chlorophyll a, carotenoids, phycobilliproteins, proteins, amino acid, nucliec acid, C/N ratio and elemental composition, carbohydrate and different enzymes at four days interval up to 16 days. According to our results, Scytonema sp. was significantly affected by the pollution with regard to the different physiological parameters examined, and this significance may be negative, positive or variable. The effect of the pollutant on carbohydrate, and the total amount of amino acids, proteins was negative, however, the composition of the phenol increase with raise in PAHs concentration. A positive effect of the pollutant on cellular C/N ratio was observed up to certain doses of PAHs. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.9784 Int J Appl Sci Biotechnol, Vol. 2(1): 34-40